2018
DOI: 10.13083/reveng.v26i2.862
|View full text |Cite
|
Sign up to set email alerts
|

EFEITOS ALELOPÁTICOS DE Sesbania virgata (CAV.) PERS NA GERMINAÇAO DE SEMENTES DE ALFACE

Abstract: As substâncias produzidas pelo metabolismo secundário das plantas podem interferir no comportamento morfológico, fisiológico e etológico de outros organismos. O objetivo deste trabalho foi avaliar o efeito alelopático do extrato aquoso de diferentes órgãos de Sesbania virgata (Cav.) Pers em sementes de alface (Lactuca sativa L, Asteraceae). Foram conduzidos quatro experimentos em laboratório num delineamento inteiramente casualizado, com quatro repetições. Cada repetição foi representada por uma caixa Gerbox c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…In a study using extracts of different concentrations of Sesbania virgata leaves, Araujo, Silva and Lima (2018) observed that there was no significant difference between the treatments in relation to the percentage of lettuce germination when compared to the control. Also based on the same study, the variable SGI showed a significant difference in the concentrations 50%, 75% and 100%; in the variable increase of the average time, the presence of the extracts increased the period for emergence of the plants and the average speed suffered a significant reduction on the interference of the extracts; and in relation to the average time the presence of the extracts increased the period for emergence of the plants and consequently the average speed decreased.…”
Section: Resultsmentioning
confidence: 99%
“…In a study using extracts of different concentrations of Sesbania virgata leaves, Araujo, Silva and Lima (2018) observed that there was no significant difference between the treatments in relation to the percentage of lettuce germination when compared to the control. Also based on the same study, the variable SGI showed a significant difference in the concentrations 50%, 75% and 100%; in the variable increase of the average time, the presence of the extracts increased the period for emergence of the plants and the average speed suffered a significant reduction on the interference of the extracts; and in relation to the average time the presence of the extracts increased the period for emergence of the plants and consequently the average speed decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Garbim et al (2015), observaram que sementes de alface sob inluência de óleo essencial de eucalipto (Eucalyptus globulus Labill) tiveram a germinação totalmente inibida na concentração 0,3%. Araujo et al (2018) verificaram que extratos aquosos das folhas e cascas do caule de Sesbania virgata (Cav.) Pers em doses crescentes (50, 75 e 100%) apresentaram interferência na velocidade de germinação de alface.…”
Section: Discussionunclassified
“…Ademais, atualmente têm-se tornado eficaz e necessário o uso de práticas agrícolas sustentáveis, com o intuito de amenizar a produção de sintéticos que além de afetar o meio ambiente, provocam malefícios ao ser humano (CAVALCANTI et al, 2015;ARAÚJO;SILVA;LIMA, 2018). Portanto, objetivou-se utilizar o óleo essencial de aroeira e avaliar o efeito alelopático a partir do bioensaio vegetal sobre sementes de alface.…”
Section: Introductionunclassified